Abstract Number: LBA1 Endovascular Thrombectomy vs Best Medical Therapy for Late Presentation Ischaemic Stroke Selected using Non‐Contrast CT - Permesh S Dhillon; Waleed Butt; Tudor G Jovin; Anna Podlasek; Norman McConachie; Robert Lenthall; Sujit Nair; Luqman Malik; Kailash Krishnan; Iacopo Chiavacci; Farhan Mehedi; Timothy Hong; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction The efficacy and safety of endovascular thrombectomy (EVT) beyond 6 hours from acute ischaemic stroke (AIS) onset for patients with proximal large vessel occlusion (LVO) selected without CT perfusion or MR imaging is undetermined in routine clinical practice. Methods In this single centre study, we identified consecutive AIS patients with an ICA or M1 MCA segment occlusion who were eligible for EVT based on non‐contrast CT/CT angiography (without CT perfusion or MR imaging) using an Alberta Stroke Program Early CT Score (ASPECTS) of ≥ 6, and an NIHSS score of≥ 6, presenting beyond 6 hours from stroke onset, between January 2018 and March 2022. During the study period, EVT capacity limitations meant EVT‐eligible patients presenting out of regular working hours (between 18.00 and 08.00 on weekdays) or on weekends, consistently received best medical management (BMM). This systemic unavailability of EVT, allows a comparison of EVT and BMM in patients who meet the same inclusion criteria, in which selection based on physician‐related bias is significantly reduced. Functional outcomes (modified Rankin Scale (mRS) at 90 days), symptomatic intracranial haemorrhage (sICH) and mortality at 90 days were compared between patients receiving EVT or BMM following multivariable adjustment for age, sex, baseline stroke severity, ASPECTS, onset‐to‐neuroimaging time, IV thrombolysis, and clot location.Pre‐specified subgroup analyses were performed. Results Among 4802 AIS patients, 150 patients (3.1%) presenting beyond 6‐hours of onset were eligible for EVT: 74 (49%) treated with EVT and 76 (51%) with BMM. Compared to the BMM group, patients treated with EVT had significantly improved functional outcome (mRS) (adjusted common OR = 2.23, 95%CI 1.18‐4.22, p = 0.013), and higher rates of functional independence (mRS≤2; 39.2.% vs 9.2%; aOR = 4.73, 95%CI 1.64‐13.63, p = 0.004). No significant difference was observed between the EVT and BMM groups in the sICH (5.4% vs 2.6%, p = 0.94) or mortality (20.2% vs 47.3%, p = 0.16) rates, respectively. EVT remained effective within the 6–12 hour and >12 hour time window subgroups. No significant treatment interaction was observed in all subgroups. Conclusions In routine clinical practice, of the 3.1% of patients in our AIS population presenting after 6 hours from stroke onset who were deemed eligible for EVT by NCCT/CTA alone, those treated with EVT achieved significantly improved functional outcome, compared to patients treated with BMM only. No significant differences were noted between the two groups with respect to sICH and mortality. While confirmatory randomised trials are awaited, these findings suggest that EVT is effective and safe when performed in AIS patients selected without CTP or MRI beyond 6 hours from stroke onset.